Questions of identity - Veljak, Lino (2011)
This issue provides a very short selection of papers presented at the international and interdisciplinary conference “Questions of Identity” (held in Cres, September 19–22, 2010 as the main theme of the 19th Days of Frane Petrić). There were more than hundred lectures given by: philosophers, including experts in ethics, logic, aesthetics, and all who strive to exceed the narrow professional framework of a discipline.
Projekt MZOS
Projekt MZOS
ENG